The MTN-016 Pregnancy Registry: Baseline Characteristics of Enrollees from the VOICE Study and Reasons for Non-enrollment of Eligible Women - Kabwigu, Samuel; Noguchi, Lisa; Moodley, Jothi; Palanee, Thes; Kintu, Kenneth; Nair, Lulu; Panchia, R.; Selepe, Pearl; Balkus, Jennifer E.; Torjesen, Kristine; Piper, Jeanna; Scheckter, Rachel; et al. (AIDS Research and Human Retroviruses, 2014)
As pregnant women are at risk for HIV and women at risk of HIV may become pregnant, it is important to assess the safety of candidate HIV prevention products in both non-pregnant and pregnant women. The MTN-016 pregnancy registry is a prospective observational cohort in which participants who became pregnant during MTN effectiveness studies or those with planned exposures in pregnancy safety studies are monitored for adverse obstetric outcomes; infants from these pregnancies are followed through the first year of life. Registry enrollment systematically excludes termination of pregnancy and early pregnancy loss, including early non-viable pregnancies with a transient positive test at a monthly visit, as these data are captured in parent protocols. For VOICE participants enrolled into the registry from Uganda, Zimbabwe and South Africa, we describe baseline demographic characteristics and key reasons for non-enrollment as reported by site investigators.
Keywords: Pregnancy Registry; VOICE Study; Eligible Women